Collective effect of rosemary (Rosmarinus officinalis) and betel (Piper betel) leaves extract on chicken powder incorporated fried chicken vermicelli. Issue 3 (21st January 2021) - Saini, Ashish; Pandey, Anurag; Sharma, Sanjita; Suradkar, Umesh Shaligram; Ambedkar, Yellamelli Ramji; Meena, Priyanka; Gurjar, Asman Singh
Abstract : Purpose: The purpose of this study is to develop chicken powder (CP) incorporated fried chicken vermicelli and to evaluate the collective effect of rosemary and betel leaf extracts (RE+BE) in developed products, on the performance of storage study parameters. Design/methodology/approach: Two different groups were made from developed products: the first control group without RE+BE incorporated and the second group treated with RE+BE (1:1). Various chemical, microbiological and sensory parameters of both groups were evaluated at intervals of 15 days up to 60 days of storage. Findings: RE+BE incorporation had significantly improved ( p < 0.01) the thiobarbituric acid reactive substances (TBARs), free fatty acid (FFA) and tyrosine value as compared to control. TBARs value of RE+BE treated product remained lower (0.23 ± 0.08 to 0.65 ± 0.07) than the control (0.25 ± 0.06 to 0.83 ± 0.05). Similarly, RE+BE treated product had significantly ( p < 0.04) lower total plate count (TPC), Staphylococcus count (SC) and significantly ( p < 0.01) lower yeast and mold count than control. Likewise RE+BE incorporation significantly ( p < 0.01) improves sensory score (texture, flavor and overall acceptability except for appearance) of the product. RE+BE treated sample at the 60th day had a higher overall acceptability score (6.3 ± 0.8) than the score of control at the 45th day (6.1 ± 0.9). Research limitations/implications: A shelf-stable meat product can be made by chicken powder incorporation in the gram flour and a combination of rosemary and betel leaf extracts may be used to improve the shelf-life of meat products. Practical implications: A shelf-stable meat product can be made by chicken powder incorporation in the gram flour and a combination of rosemary and betel leaf extracts may be used to improve the shelf-life of meat products. Originality/value: RE+BE incorporation into chicken vermicelli improved chemical (TBARs, FFA content and Tyrosine value), microbiological (TPC, Staphylococcus count and yeast and mold count) and sensory (flavor, texture and overall acceptability) parameters of chicken vermicelli during 60-day storage.